1999
DOI: 10.1002/(sici)1097-461x(1999)73:4<349::aid-qua4>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of single-bonded nitrogen cluster-type molecules

Abstract: Nine single-bonded nitrogen cluster-type molecules N x s 8᎐24 were x investigated using the B3LYPr6-31G** DFT method. Geometrical optimization, vibrational frequencies, and thermal chemical calculation of these molecules were compared. All the molecules were proved to be local minima. The coordination number three of all atoms and bond distances at around 1.5 A indicate that all the molecules were Ž . constructed with single bonds. A comparison of the average bond energy BE s ⌬ H rn , a B Ž . Ž Ž . . single-bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…The structure of ZT 2with C2h symmetry in this figure is quite similar to the structure which resulted experimentally as recently reported by Hammerl et al 27 As for the combined GZT molecular system, we, in order to proceed with the geometrical adjustment type SCF calculation, started our input structure data by setting one of the carbon atoms in G + with a near-planar D 3 structure above the five-member ring center in ZT 2-, and the other carbon atoms below the other five-member ring center in the same anion, ZT. [2][3][4][5][6][7][8][9][10] After a time-consuming but adjustable optimization procedure, GZT with a near-planar type structure with C i symmetry, as shown in Fig. 2, was obtained.…”
Section: Geometrical Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The structure of ZT 2with C2h symmetry in this figure is quite similar to the structure which resulted experimentally as recently reported by Hammerl et al 27 As for the combined GZT molecular system, we, in order to proceed with the geometrical adjustment type SCF calculation, started our input structure data by setting one of the carbon atoms in G + with a near-planar D 3 structure above the five-member ring center in ZT 2-, and the other carbon atoms below the other five-member ring center in the same anion, ZT. [2][3][4][5][6][7][8][9][10] After a time-consuming but adjustable optimization procedure, GZT with a near-planar type structure with C i symmetry, as shown in Fig. 2, was obtained.…”
Section: Geometrical Optimizationmentioning
confidence: 99%
“…We then published our paper on the "Theoretical Study of the High-energy Molecules or Clusters Constructed with Pure Nitrogen Atoms, Nn (n = 8 to 32)". [1][2][3][4][5][6][7] However, these theoretically predicted substances, so-called stable pure nitrogen molecular clusters, have still not been found. In the past decade, several important stable nitrogenrich compounds have been invented for gas-generating mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…A significant number of theoretical papers in recent years have also been devoted to the search for structures of isolated nitrogen clusters N m with m ≥ 3. The structural and energy characteristics of N 3 − [15], N 4 [16, 17,18], N 5 − [19,20], N 5 + [20,21], N 6 [17,18], N 8 [18,22], N 10 [23,24], N 12 [25,26], N 14 [25], N 16 [25], N 18 [25], N 20 [25,27], N 24 [25,28,29], N 30 [28,29], N 32 [29], N 36 [28,29], N 40 [29], N 42 [29], N 48 [29], N 54 [29], N 56 [29], N 60 [1,29,30], N 72 [31], N 78 [32] clusters are studied in detail. Among these clusters, it is worth noting the experimentally synthesized tetranitrogen N 4 [16], azide anion N 3 − [15], pentanitrogen cation N 5 + [21], and pentanitrogen anion N 5 − [19] that was only detected in the gas phase.…”
Section: Introductionmentioning
confidence: 99%
“…They also suggested some potential polynitrogen molecules. [20][21][22][23][24][25][26][27][28] Noyman et al [29] studied some polynitrogen molecules from the perspective of wave function analysis and they concluded that when several nitrogen atoms link directly, the repulsive interaction between the lone electron pairs on the adjacent nitrogen atoms is very strong, the r orbitals and p orbitals in a polynitrogen molecule cannot be separated efficiently, and this restrains the formation of polynitrogen molecule. The introduction of coordinated oxygen atoms can weaken the repulsive interaction and separate the r orbitals from the p orbitals efficiently.…”
Section: Introductionmentioning
confidence: 99%